Qassem Soleimani, Targeted Killing of State Actors, and Executive Order 12,333 - Molloy, Taran (Victoria University of Wellington Law Review, 2021)
The targeted killing of the Iranian military leader Qassem Soleimani in an American drone strike in January 2020 marked a novel development in the operation of the United States’ drone programme; targeting a member of a state’s armed forces as opposed to a member of a non-state armed group. Soleimani’s killing offers an opportunity to re-examine the scope of Executive Order 12,333, which prohibits employees of the United States Government from committing assassinations. This article applies Executive Order 12,333’s "assassination ban" to the Soleimani strike. The assassination ban’s scope varies depending on whether it is applied in a wartime or peacetime context. This article concludes from the surrounding factual and legal context that the strike should be analysed according to the peacetime definition of assassination, which necessitates an analysis of the strike’s compliance with the jus ad bellum, the legal framework applicable to uses of interstate force. It finds that the strike’s non-compliance with the jus ad bellum, in addition to its likely political motive create a strong argument that the strike would constitute a prohibited assassination under the terms of the Executive Order, but the legal framework surrounding the Executive Order limits its direct enforceability with respect to presidentially authorised uses of force. It ultimately concludes that, despite the assassination ban’s lack of direct enforceability, it nevertheless creates a strong normative counterbalance against an increasing tendency toward expansive uses of extraterritorial force.